Standards for the provision of antenatal care for patients with inflammatory bowel disease: guidance endorsed by the British Society of Gastroenterology and the British Maternal and Fetal Medicine Society. Issue 3 (7th May 2020) - Selinger, Christian; Carey, Nicola; Cassere, Shelley; Nelson-Piercy, Catherine; Fraser, Aileen; Hall, Veronica; Harding, Kate; Limdi, Jimmy; Smith, Lyn; Smith, Marie; Gunn, Melanie Catherine; Mohan, Aarthi; et al.
Abstract : Background: Pregnant women with inflammatory bowel disease (IBD) are at increased risk of adverse pregnancy outcomes. Comprehensive guidelines on medical management have been published; yet, there is limited guidance on service set-up and minimum standards of care for pregnant women with IBD. Aim: To develop a position statement on service set-up and minimum standards of care in the UK. Methods: A working group consisting of 16 gastroenterologists, obstetricians, obstetric physician, IBD specialist nurses and midwives was assembled. Initial draft statements were produced and a modified Delphi process with two rounds of voting applied. Statements were modified according to voters' feedback after each round. Statements with ≥80% agreement were accepted. Results: All 15 statements met criteria for inclusion. To facilitate optimal care, regular and effective communication between IBD and obstetric teams is required. There should be nominated link clinicians for IBD in obstetric units and for pregnancy in IBD units. Preconception counselling should be available for all women with IBD. All pregnant women should be advised on the safety of IBD medication during pregnancy and breast feeding, the optimal mode of delivery, the management of biologics (where applicable) and safety of childhood vaccinations. Regular audit of pregnancy outcomes and documentation of advice given is recommended. Conclusion: Position statements have been developed that advise on the importance of joined-up multidisciplinary care, proactive decision-making with clear documentation and communication to the woman and other healthcare practitioners.